Spatial transformations in Ceuta (Spain). Effects of a low density hinterland on a border enclave - Cimadomo, Guido (My University, 2018)
Located in a strategic geopolitical settlement on the north coast of Africa, the enclave of Ceuta is a highly researched border settlement, due to its specificity and being the unique tangible border between the EU and Africa. What is less studied is the urban development of the city, which is needed to understand the evolution of this city in relation with the border area. The uniqueness of this case, caused by the decision of the Kingdom of Morocco not to recognize the border, is related with a lack of urban development and any density on the Moroccan side of the 8 km fence. This fence is one of the few examples in the world and is considered of great interest. In such a situation migratory and economic flows need to adapt to written and unwritten laws. The border can hence be considered a permeable membrane for informal economic activities, while it becomes a strong barrier to limit undesired flows. This limit can be considered an opportunity, also considering the reduced ground where to grow, as urban planning decisions taken at a local level can improve the territorial continuity already existing at both sides of the border, and reduce social and spatial injustices. Also if centripetal strategies to densify and improve the built environment, with evident marginalization of the periphery, are envisioned in the new plan, we foresee the opportunities to significantly improve community conditions, being at the local level where answers to social and neighbour problems can be found.
Keywords: Urbanismo; España - Fronteras - Marruecos; Ceuta; Borderscapes; Urban transformations; Borderland development; Urban planning